Pengaruh Strategi Pemasaran dan Manajemen Merek terhadap Kinerja UMKM di Era Media Digital : Studi Kasus UMKM Di Kota Tasikmalaya - Syifaul Munawaroh; Alfin Nur Arifah; Yudi Setia Rachmanda; Rina Madyasari (Pusat Riset dan Inovasi Nasional, 2026)
The rapid expansion of the digital economy has simultaneously generated new market opportunities and intensified competitive pressures for micro, small, and medium enterprises (MSMEs). In Tasikmalaya City, home to 2,942 registered active MSMEs, a preliminary survey conducted among 20 business owners revealed that marketing capabilities, brand management practices, and overall business performance were all assessed at low levels, underscoring the need for empirical investigation. This study was therefore designed to examine the extent to which marketing strategy and brand management influence MSME performance within the context of the digital media landscape. A quantitative methodology with an associative-causal design was employed. Data were gathered from 97 purposively selected respondents using a Likert-scale questionnaire instrument. Multiple linear regression analysis was conducted following verification of all classical assumption criteria. The findings demonstrate that marketing strategy (β = 0.541, t = 7.579, p = 0.000) and brand management (β = 0.429, t = 6.016, p = 0.000) each exert a positive and statistically significant effect on MSME performance. Jointly, these two predictors account for 52.6% of the variance in MSME performance (R² = 0.526), with the overall model confirmed as fit (F = 52.238, p = 0.000). These results reinforce the applicability of Resource-Based View theory and Brand Equity Theory to small business contexts, and suggest that digital marketing literacy alongside deliberate brand-building efforts are critical drivers of sustained competitive advantage for MSMEs in an increasingly digital business environment.